Pendidikan Karakter Sebagai Aksiologi Menurut Filsafat Ilmu - Arofah, Siti; Silalahi, Suandi (UNTIRTA CIVIC EDUCATION JOURNAL, 2024)
Education becomes the main foundation in facing the transformation of the 21st century which is marked by technological advances and rapid changes. Adaptation to these developments is needed to create individuals who are able to contribute to a dynamic global society. Therefore, the philosophy of education must be relevant to the needs of the times, especially in terms of epistemology and axiology. This study uses a library method with a literature review technique to analyze the role of character education as an axiology in the philosophy of science. Data sources include relevant books and journals. Discussion and results of the study show that 21st century education is not only oriented towards theory but also the integration of technology and inclusive skills. The philosophy of education serves as a guide to ethical values and the direction of education. The evolution of educational concepts from time to time shows the importance of adapting to change to form critical-thinking individuals in this technological era.